2020
DOI: 10.1007/s10238-020-00617-4
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin-3 is not related to disease severity in cirrhosis and hepatocellular carcinoma patients

Abstract: The acute-phase protein pentraxin-3 (PTX3) is a component of the innate immune system. Inflammation and tissue injury increased PTX3 in the injured liver, and accordingly, circulating PTX3 was induced in patients with chronic liver diseases. In the present study, PTX3 protein was determined in systemic, hepatic, and portal vein plasma of patients with liver cirrhosis to assess a possible association between hepatic PTX3 release and extent of liver injury. However, PTX3 levels were not related to disease severi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
(74 reference statements)
1
12
2
Order By: Relevance
“…However, expression levels of PTX3 vary among HCC cell lines, 26 and it is considered to have no diagnostic value in HCC patients because its expression is not related to the TNM classification of HCC. 27 The results of the current UALCAN analysis also found no relationship between PTX3 expression level and tumor grade or survival prognosis in HCC patients (data not shown). This suggests that SPOCD1 may promote HCC tumorigenesis through a PTX3-independent pathway.…”
Section: Discussionmentioning
confidence: 73%
“…However, expression levels of PTX3 vary among HCC cell lines, 26 and it is considered to have no diagnostic value in HCC patients because its expression is not related to the TNM classification of HCC. 27 The results of the current UALCAN analysis also found no relationship between PTX3 expression level and tumor grade or survival prognosis in HCC patients (data not shown). This suggests that SPOCD1 may promote HCC tumorigenesis through a PTX3-independent pathway.…”
Section: Discussionmentioning
confidence: 73%
“…[18][19][20]34 It should be noted that there is a study showing that PTX3 is not related to disease severity in cirrhosis and HCC patients. 35 However, this study included relatively small number of cirrhosis (n=35) and HCC (n=31) patients. 35 More other studies confirmed the potential of PTX3 as a biomarker in evaluating the disease severity and prognosis of cirrhosis 36 and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, this study included relatively small number of cirrhosis (n=35) and HCC (n=31) patients. 35 More other studies confirmed the potential of PTX3 as a biomarker in evaluating the disease severity and prognosis of cirrhosis 36 and HCC. [18][19][20]34 The present study showed that increased serum PTX3 levels were associated with poor prognosis of HBV-related HCC and high PTX3 level was an independent factor associated with a reduced survival time of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…During TIPS, EDTA plasma was obtained from the hepatic vein (HVP), the portal vein (PVP) and from a peripheral vein (SVP). These blood samples were used in former studies [31][32][33][34][35] Medicine. Analysis of cholesteryl ester and sphingolipid species in our patients with liver cirrhosis has been done before and data were published [36].…”
Section: Patientsmentioning
confidence: 99%
“…The human PCSK9 DuoSet ELISA was used (R&D Systems; Wiesbaden, Nordenstadt, Germany) as specified by the provider (dilution 1:100). Resistin, galectin-3, IL-6, adiponectin, leptin, chemerin and pentraxin 3 were measured in serum / plasma before [31][32][33][34][35].…”
Section: Pcsk9 Elisamentioning
confidence: 99%